Characterization of the Lipid Fraction of Cocoplum Seeds (Chrysobalanusicaco, L) for Use in the Food Industry - Mello, Andrea A.; Azevedo-Meleiro, Cristiane Hess; Oliveira Sabaa-Srur, Armando Ubirajara; Grimaldi, Renato; Smith, Robert E. (Natural Products Journal, The, 2017)
Background: The cocoplum (Chrysobalanus icaco, L) is in the Chrysobalanaceae family. It has a pantropical distribution, with 18-20 genuses and at least 500 species. This family is comprised of trees and shrubs, with alternating, simple leaves with stipules (small and deciduous). Objective: The objectives of this study were to determine: (1) the fatty acid profile in cocoplum (Chrysobalanus icaco, L) seed oil by High Resolution Gas Chromatography (HRGC), (2) the melting point by Differential Scanning Calorimetry (DSC). In addition, the relatively high concentration of unsaturated fats makes it a potentially nutritious food. This includes oleic acid (C18:1) and a low concentrations of lauric (C12:0), myristic (C14:0) and palmitic (C16:0) acids. Method: HRGC and DSC. Results: The melting point of 24.29 ºC makes this a vegetable oil. Conclusion: Since it has 4 to 5% solids at body temperature (36.5 to 37 °C), it would be useful in the food industry.
Keywords: Chrysobalanus icaco